2003
DOI: 10.1128/jvi.77.2.1571-1577.2003
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Dual Recombinant Vaccine To Protect Small Ruminants against Peste-des-Petits-Ruminants Virus and Capripoxvirus Infections

Abstract: A recombinant capripoxvirus vaccine containing a cDNA of the peste-des-petits-ruminants virus (PPRV) fusion protein gene was constructed. A quick and efficient method was used to select a highly purified recombinant virus clone. A trial showed that a dose of this recombinant as low as 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 29 publications
2
64
0
Order By: Relevance
“…A VACV double recombinant expressing H and F glycoproteins of RPV has been shown to protect goats against PPR [67] though the animals developed virus-neutralising antibodies only against RPV and not against PPRV. Capripox recombinants expressing the H or F protein of RPV or the F protein of PPRV conferred protection against PPR in goats, but without production of PPRV-neutralizing antibodies [115] or PPRV antibodies detectable by ELISA [22]. Results of these studies suggested that cell-mediated immune responses could play a crucial role in the protection.…”
Section: Immunitymentioning
confidence: 68%
See 1 more Smart Citation
“…A VACV double recombinant expressing H and F glycoproteins of RPV has been shown to protect goats against PPR [67] though the animals developed virus-neutralising antibodies only against RPV and not against PPRV. Capripox recombinants expressing the H or F protein of RPV or the F protein of PPRV conferred protection against PPR in goats, but without production of PPRV-neutralizing antibodies [115] or PPRV antibodies detectable by ELISA [22]. Results of these studies suggested that cell-mediated immune responses could play a crucial role in the protection.…”
Section: Immunitymentioning
confidence: 68%
“…The H and F protein genes of several morbilliviruses have been expressed in various vector systems and they can be used as effective sub-unit vaccines. Following this approach, the F protein of PPRV was inserted into the genome of an attenuated capripox vaccine virus candidate [22]. The resulting recombinant virus expressed the PPRV F protein on the surface of infected cells, which was recognized by an anti-F MAb.…”
Section: Recombinant Vaccinesmentioning
confidence: 99%
“…The common immunogenic properties of these viruses have been used for the preparation of live attenuated vaccines that protect all ruminants against CaPV infection (Kitching et al, 1987). Recombinant CaPVs have also been developed for multivalent vaccination purposes (Berhe et al, 2003;Perrin et al, 2007;Romero et al, 1993;Wade-Evans et al, 1996;Wallace et al, 2006). However, although they are antigenically closely related, restriction enzyme pattern analysis, cross-hybridization studies and, more recently, nucleic acid sequencing have shown that nearly all CaPVs can be grouped according to their host origins Cao et al, 1995;Gershon & Black, 1988;Kitching et al, 1989;Tulman et al, 2002).…”
mentioning
confidence: 99%
“…The use of filtration and sonication to select for homogeneous LSDV recombinants has proven reproducible and successful in the hands of others (Berhe et al, 2003) and at present remains the method of choice in our laboratory. Advances in selection strategies, which promise to make the selection for homogeneous recombinants even more efficient, such as described by Timiryasova et al (2001), are currently under investigation for use with LSDV.…”
Section: Discussionmentioning
confidence: 99%
“…As for other members of the Poxviridae family, attenuated vaccine strains of LSDV are being developed as vectors for recombinant vaccines for use in the veterinary field. The Kenya Sheep-1 strain, KS-1 ( [Kitching et al, 1987] and [Kitching et al, 1989]), has been utilised for the development of recombinant rinderpest, bluetongue and peste-des-petits-ruminants virus vaccines ( [Romero et al, 1993], [Romero et al, 1994a], [Romero et al, 1994b], [Romero et al, 1994c], [WadeopenUP (December 2007) Evans et al., 1996], [Ngichabe et al, 1997] and [Berhe et al, 2003]). The southern African LSDV vaccine strain, SA-Neethling, was developed from a virulent field isolate, and is a highly host-restricted vaccine that offers long-term protection (Weiss, 1968).…”
Section: Introductionmentioning
confidence: 99%